Trump the presidential photographs : selections from the Official White House photography - William Morrow and Company (New York William Morrow, an imprint of HarpercollinsPublishers, 2020)
A collection of photographs of President Donald Trump, the First Family, and the 45th presidency, taken by the Official White House Photographers, accompanied by selected quotes from presidential speeches and remarks.
108870
Keywords: Trump, Donald, -- 1946- -- Pictorial works; Trump, Donald, -- 1946- -- Quotations; Since 2017; Presidents -- United States -- Pictorial works; Politics and government; United States -- Politics and government -- 2017- -- Pictorial works; Illustrated works; Pictorial works; Quotations